Odpowiedzi

Najlepsza Odpowiedź!
2010-02-27T22:57:28+01:00
Y= -1/3x -2
A = (4; -4)
y=cx+d
c= -1/a = -1/(-1/3) = -1*(-3) = 3
y = 3x + d
-4 = 3*4 +d
-4 = 12 +d
-16 = d
y = 3x -16 (prosta prostopadła do y= -1/3x -2)
3x - 16 = -1/3x -2
3 1/3 x = 14
10/3 x = 14
10x = 42
x = 4,2
y = 3*4,2 - 16
y = 12,6 - 16
y = -3,4
P = (4,2 ; -3,4) <--- punkt przecięcia prostych prostopadłych

B= (x,y)
P=[(4+x)/2 ; (-4+y)/2)
4,2 = (4+x)/2 ; -3,4 = (-4+y)/2
4+x = 8,4 ; -4+y = -6,8
x= 4,4 ; y = -2,8
B = (4,4 ; -2,8)
7 2 7